A meshless method for modeling the microscopic drying shrinkage cracking processes of concrete and its applications. (January 2023) - Yu, Shuyang; Sun, Zhaohua; Qian, Wangping; Yu, Jun; Yang, Jie
Highlights: The traditional smoothing kernel function in SPH method has been improved to realize the progressive failure processes of concrete. The random aggregate generating method and the "region searching" method have been proposed to realize the generations of concrete meso -structures in SPH. The SPH forms of humidity conduction equations have been derived, which can realize the simulations of humidity expansions in SPH. The relationships between the humidity gradient and concrete shrinkage stress is defined, which is embedded into SPH constitutive equations to realize the simulations of concrete humidity – stress- damage coupling problems. Abstract: The dry shrinkage cracking of concrete structures has a great influence on their mechanical strengths. However, traditional numerical methods have some limitations in dealing with the shrinkage cracking processes of concrete. Based on this background, the traditional smoothing kernel function in Smoothed Particle Hydrodynamics (SPH) method has been improved, which can realize the simulations of progressive cracking processes of concrete; The SPH forms of humidity conduction equations have been derived, which can realize the simulations of humidity expansions in SPH; The relationships between the humidity gradient and concrete shrinkage stress is defined, which is embedded into SPH constitutive equations to realize the simulations of concrete humidity – stress- damage coupling problems; The random aggregate generating method and the "region searching" method have been proposed to realize the generations of concrete meso -structures in SPH. Firstly, the microscopic dry shrinkage cracking processes of a circular concrete model is simulated, and the rationality of the improved method is verified by the comparisons with previous experimental results. Then the influences of different factors (aggregate percentages, ambient humidity, shrinkage coefficient and moisture diffusivity) on the dry shrinkage cracking morphologies as well as the moisture transfer mechanisms of concrete are systematically discussed, results show that: The aggregate percentage affects the depths the "advantage cracks" penetrate into the concrete model; With the decrease of ambient humidity and moisture diffusivity, the density of shrinkage cracks increase sharply, and the crack length also increases; The penetration depth of the "advantage cracks" increases with the increase of the shrinkage coefficient. The research results can provide some references for the comprehensive understandings of the mechanisms of concrete shrinkage cracking and moisture migration. Meanwhile, it can also provide a certain understanding for the applications of SPH method into simulations of humidity – stress- damage coupling problems.